2014
DOI: 10.3109/09553002.2014.874608
|View full text |Cite|
|
Sign up to set email alerts
|

Abscopal effect of radiation therapy: Interplay between radiation dose and p53 status

Abstract: We suggest that the interplay between delivered dose and p53 status might help to sterilize out-of-field tumour cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…Xie et al reported that the phosphorylation of p53 could result in increased radiosensitivity and the inhibition of tumor reproduction [26]. Strigari et al also demonstrated that p53-dependent signals might be responsible for the abscopal effect in RT to sterilize nonirradiated tumor cells through a proapoptotic pathway [27]. These outcomes were also compatible with our results that the overexpression of p53 enhanced the radiation-induced G2/M phase arrest of OC3 cells.…”
Section: Discussionsupporting
confidence: 92%
“…Xie et al reported that the phosphorylation of p53 could result in increased radiosensitivity and the inhibition of tumor reproduction [26]. Strigari et al also demonstrated that p53-dependent signals might be responsible for the abscopal effect in RT to sterilize nonirradiated tumor cells through a proapoptotic pathway [27]. These outcomes were also compatible with our results that the overexpression of p53 enhanced the radiation-induced G2/M phase arrest of OC3 cells.…”
Section: Discussionsupporting
confidence: 92%
“…With the exception of immunogenic cell death, this is still largely unexplored terrain. Two preclinical models suggest p53 as a key mediator for abscopal effects [38, 39]. In clinical research, a couple of the mentioned papers also explored individual markers in abscopal responses.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, the most rational explanation of the abscopal effect is the concept of ICD. One of the major effects ICD can unleash an effective immune response is induction of a strong “danger signal” generated by damaged tissue under endoplasmic reticulum stress [22]. Dying tumor cells succumbing to ICD induce danger signals called “alarmins” that have immunogenic properties.…”
Section: Discussionmentioning
confidence: 99%